(untitled) (Research, Society and Development, 2021)
The construction industry uses abundant non-renewable raw materials, consumes large amounts of energy in the extraction of inputs, in the production of materials, in the transport of both and generates an infinity of rubble in the execution of the works. Ecological adobe bricks can be manufactured using non-toxic urban waste, including civil construction. This work aimed to describe the manufacturing process and the structural characterization of ecological bricks of the adobe type using as a matrix the argisol and the oxisol, and as a binder, recyclable materials from the selective urban collection (PET and EPS), plaster discarded by the civil construction and the vinasse from the sugarcane industry. Studies were carried out on the manufacturing process of ecological brick prototypes and on the mechanical characterization water absorption, dry density, resistance to mechanical compression; stress/strain behavior, mass behavior/compressive strength. The results showed that the excessive inclusion of recyclable materials in the manufacture of adobes promotes an increase in mechanical resistance, but also increases the absorption of water in a way that does not meet the regulation of the Brazilian standard that provides for the solid brick of soil-cement. The most promising bricks were those made with 55 and 39.5% recyclable materials for the argisol and oxisol respectively.